Life or death: what factors impact the decision? - Pollock, Wendi K. (Crime, law and social change, 2021)
Death penalty cases are among the more controversial and costly. There are numerous factors that may influence a prosecutor’s decision to seek the death penalty in a capital murder case. This study considers offender demographics, district attorney characteristics, victim characteristics, local political and criminal climate, and county financial condition to gain a more holistic understanding of prosecutorial decisions surrounding the death penalty. Using multilevel logistic regression models, Texas death penalty cases from 2007 to 2018 (N = 436) were analyzed. Findings suggest a reduction in prosecutor decisions to seek the death penalty over time, and that prosecutors may be more likely to seek the death penalty if a higher percentage of victims killed were White.